PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION (PBI) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 011 PEMATANG INDAH KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU - Wahyuni, Wahyuni; Daud, Damanhuri; Alim, Jesi Alexander (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak: The problem in this reasearch is the low student learning with an everage of 66,42. autcomet. The are still many student who have not reached KKM that has been set by the school. Of 7 student only 2 students who completed (28,57%). The subjects were fourth grade student IV of SD Negeri 011 Pematang Indah Kecamatan Kelayang Kabupaten Indragiri Hulu. With the number of student 7 student. Based on these problems it is recessary of find a way to soluo problem. Problem based instruction (PBI) provide an opportunity for student to learn in pleasant atmosphere. Involuing student directly in the learning in order to inprove students learning autcomes. Classes IV SD Negeri 011 Pematang Indah. The reaserch was conducted in two cycles with for meetings and two replication. And of the cycle instrument collecting data in this study is the observation. Sheet student teacher observation sheet and repeat the test and of the cycles. The study is in the form of in classroom action reasearch (PTK). Aim to improve student learning autcomes. These result indicate that the problem based learning model of instruction (PBI) can improve autcomes IPA grade IV SD Negeri 011 Pematang Indah Kecamatan Kelayang Kabupaten Indragiri Hulu. Of this basic scor with an everage by an everage of 66,42. Cycly I increase IV by an everage of everage 77,14 and at cycle II increase the everage with an everage of 93,57. Their full vield increase was 40,87%. Thus if can be conduted that the hypotesis is â€œ if applied learning model of problem based instruction (PBI). Then it can improve learning autcomes IPA grade IV SD Negeri 011 Pematang Indah Kecamatan Kelayang Kabupaten Indragir Huluâ€ acceptableKeyword : Learning model problem based instruction (PBI), IPA learning result.